2004
DOI: 10.1128/aem.70.5.2647-2652.2004
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of Immunity Proteins of Pediocin-Like Bacteriocins: C-Terminal Parts of Immunity Proteins Are Involved in Specific Recognition of Cognate Bacteriocins

Abstract: The immunity proteins of pediocin-like bacteriocins show a high degree of specificity with respect to the pediocin-like bacteriocin they recognize and confer immunity to. The aim of this study was to identify regions of the immunity proteins that are involved in this specific recognition. Six different hybrid immunity proteins were constructed from three different pediocin-like bacteriocin immunity proteins that have similar sequences but confer resistance to different bacteriocins. These hybrid immunity prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…Later, the structure of subgroup B immunity protein (piscicolin 126-im) was shown to have the conserved fourhelix bundle but relatively shorter and less flexible C-terminal part (Martin-Visscher et al 2008). Structural studies on hybrid immunity proteins proposed that the C-terminal parts of the immunity proteins determine the immunity and specific recognition of the C-terminal hairpin of class IIa bacteriocins (Johnsen et al 2004;Johnsen et al 2005a). Moreover, piscicolin 126 immunity protein contains a C-terminal hydrophobic pocket comprising residues that are highly conserved in subgroup B immunity proteins (Martin-Visscher et al…”
Section: Bacteriocin Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the structure of subgroup B immunity protein (piscicolin 126-im) was shown to have the conserved fourhelix bundle but relatively shorter and less flexible C-terminal part (Martin-Visscher et al 2008). Structural studies on hybrid immunity proteins proposed that the C-terminal parts of the immunity proteins determine the immunity and specific recognition of the C-terminal hairpin of class IIa bacteriocins (Johnsen et al 2004;Johnsen et al 2005a). Moreover, piscicolin 126 immunity protein contains a C-terminal hydrophobic pocket comprising residues that are highly conserved in subgroup B immunity proteins (Martin-Visscher et al…”
Section: Bacteriocin Immunitymentioning
confidence: 99%
“…Besides, the function of immunity protein has been found to be strain-dependent (Johnsen et al 2005a). Therefore, instead of direct binding to the bacteriocins, the immunity proteins may interact with a receptor protein which varies in different strains (Figure 2 and Figure 3, p30) (Fimland et al 2002a;Johnsen et al 2004). …”
Section: ) As Hydrophobic Interactions Are Normally Involved In mentioning
confidence: 99%
“…The immunity proteins show a high degree of specificity with respect to the bacteriocin they recognize, although some immunity proteins render cells immune to a few pediocin-like bacteriocins in addition to their cognate bacteriocin (22). Using hybrid immunity proteins and hybrid bacteriocins, it was recently shown that the C-terminal half of the immunity proteins contains a region that is involved in specific recognition of the C-terminal hairpin-like domain of the bacteriocin they confer immunity to (15,23). The mode of action of the immunity proteins is not known, but their effectiveness is strain-dependent, and the functionality of the immunity proteins thus appears to depend partly on strain-dependent factors (22,23).…”
mentioning
confidence: 99%
“…The branes; exposing the proteins to lipid micelles does not induce gross alterations in the protein conformation (23). The threedimensional structure of the pediocin-like immunity protein for carnobacteriocin B2 has recently been determined by NMR spectroscopy (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation